(untitled) (Applied Biological Research, 2017)
A study was conducted for 150 days to assess the effect of high energy diet on the performance of cross bred cows in early lactation. Crossbred cows were divided into 3 groups of 6 each. The cows in 2ndand 3rd groups were supplemented daily with 1 and 2 kg energy supplement (ground maize), respectively. Animal in all groups showed similar plasma biochemical profile viz., blood urea nitrogen, plasma calcium, plasma inorganic phosphorus, plasma magnesium, iron and plasma copper; whereas plasma glucose was high in both maize supplemented groups. The animals supplemented with 1 kg maize attained post- partum heat earlier. Though supplementation of ground maize at 1 and 2kgcow-1 day-1 did not affect plasma biochemical profile or reproductive performance significantly. Supplementation of ground maize at 1 kg day-1 cow-1 resulted in higher plasma glucose and reduced the days to first post-partum service.